Sources of Error in Blood Pressure Measurement Using Digital and Aneroid Tensimeters - Zuhdi, Muhammad; Busyairi, Ahmad (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
A tensimeter is an instrument works with concept of physics used to measure blood pressure. The measured blood pressure is the relative pressure between the pressure inside the blood vessels compared to the pressure of the atmosphere. Blood pressure measurements using a digital tensimeter are much more acurate than measurements using a aneroid tensimeter. Measurements with an aneroid sphygmomanometer at a hospital in the city of Mataram showed a measurement error up to 20 mmHg compared to a digital sphygmomanometer. Source of error consist of two main factors ie. Instrument error and human error. From this research it was found that measurements using a digital sphygmo-manometer are more accurate, so the use of this type of sphygmomanometer is highly recommended for clinical measurements in hospitals and health hospitals.